Analysis of Errors in the Use of Prefixes in Negotiation Texts of Grade X Students of Vocation High School - Nur Intan Siregar; Devinna Riskiana Aritonang; Nikmah Sari Hasibuan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to describe the errors in the use of prefixes in negotiation texts of class X students of SMK Negeri 1 Sipirok. The method used is descriptive qualitative. The data are in the form of negotiation texts written by 26 class X Hospitality students with 11 male students and 15 female students. The results of the study show that there are 38 errors in the use of prefixes, namelydi- by 47.4%, me- 26,3%,to- 15,8%, Andter- 10.5%. Errors are caused by a lack of understanding of morphological rules and the influence of spoken language.